Strategy For Improving E-Service Quality in Increasing Purchasing Decisions on The Kopi Kenangan Application - Niswan, Ramandha; Manurung, Alifia Nasya; Marliyah, Marliyah; Dharma, Budi (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
Digital marketing is a key element in business success in the modern era, with e-service quality being a crucial factor in influencing consumer satisfaction and purchasing decisions. This study aims to analyze the effect of e-service quality on product purchasing decisions through the Kopi Kenangan application. The method used is in-depth interviews and service learning with consumers and Kopi Kenangan management in the Medan area. The results show that service reliability, ease of use, and transaction security are the main factors in purchasing decisions. Education on improving digital service quality through training is proven to increase consumer and seller trust, which leads to increased loyalty and sales. This article concludes that Kopi Kenangan must continue to improve e-service quality to maintain competitiveness and maintain customer loyalty amidst increasingly fierce industry competition.